INTEGRITAS DIRI DALAM MENGHINDARI TINDAKAN INTERNET PLAGIARISM - Fadlillah, Alnisa Min (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to determine the integrity of students in avoiding internet plagiarism and how to strengthen the integrity of students in order to prepare and produce the next generation of quality nation. The number of respondents in the study was 10 seventh semester students with the selection of respondents that they had completed the assignment given by the lecturers. This study uses qualitative research methods with a phenomenological approach. The results of the analysis show that in general student integrity is still low so it needs to be strengthened in terms of integrating education, law enforcement, infrastructure, involvement of university and faculty leaders, lecturers and administrative staff who support the anti-plagiarism environment that will create culture and awareness in each university residents especially students.